Answer:
see explanation
Explanation:
The general expansion of (a + b)² is
(a + b)² = a² + 2ab + b²
Applying this to the following expansions
(1)
(x + 2)² = x² + 2(2x) + 2² = x² + 4x + 4 ← missing term is x²
(2)
(2x - 3)² = (2x)² + 2(2x)(- 3) + 3² = 4x² - 12x +9 ← missing term is - 12x
(3)
(3x + 4)² = (3x)² + 2(3x)(4) + 4² = 9x² + 24x + 16 ← missing term is 16
(4)
(x - y)² = x² + 2(x)(- y) + y² = x² - 2xy + y² ← missing term is x²
(5)
(2x + 3y)² = (2x)² + 2(2x)(3y) + (3y)² = 4x² + 12xy + 9y² ← missing term is + 12xy